Evaluating Investments in Typhoid Vaccines in Two Slums in Kolkata, India - Cook, Joseph; Sur, Dipika; Clemens, John; Whittington, Dale (Journal of Health, Population and Nutrition, 2010)
New-generation vaccines against typhoid fever have the potential to reduce the burden of disease in areas where the disease is endemic. The case for public expenditure on typhoid Vi polysaccharide vaccines for two low-income, high-incidence slums (Narkeldanga and Tiljala) in Kolkata, India, was examined. Three measures of the economic benefits of the vaccines were used: private and public cost-of-illness (COI) avoided; avoided COI plus mortality risk-reduction benefits; and willingness-to-pay (WTP) derived from stated preference (contingent valuation) studies conducted in Tiljala in 2004. Benefits and costs were examined from a social perspective. The study represents a unique opportunity to evaluate typhoid-vaccine programmes using a wealth of new site-specific epidemiological and economic data. Three typhoid-vaccination strategies (targeting only enrolled school children, targeting all children, and targeting adults and children) would most likely pass a social cost-benefit test, unless benefits are restricted to include only avoided COI. All three strategies would be considered ‘very cost-effective' using the standard comparisons of cost per disability-adjusted life-year avoided with per-capita gross domestic product. However, at an average total cost per immunized person of US 1.1, a typhoid-vaccination programme would absorb a sixth of existing public-sector spending on health (on a per-capita basis) in India. Because there appears to be significant private economic demand for typhoid vaccines, the Government could design a financially-sustainable programme with user-fees. The results show that a programme where adults pay a higher fee to subsidize vaccines for children (who have higher incidence) would avoid more cases than a uniform user-fee and still achieve revenue-neutrality. Key words: Costs and cost analysis; Cost-benefit analysis; Evaluation studies; Slums; Typhoid; Typhoid vaccine; India DOI: 10.3329/jhpn.v27i6.4319 J Health Popul Nutr 2009 Dec; 27(6): 711-724